THE TEACHING OF MARTIAL ARTS AT THE PHYSICAL EDUCATION CLASSES: A PROPOSAL OF CURRICULAR ORGANIZATION (Fiep Bulletin - online, 2011)
The fights and martial arts are each time more gifts in the present time by means of diverse ways of information, they configure - as one of the blocks of knowledge of disciplines Physical Education in the school. In this way they are gifts in the pertaining to school context while curricular content of disciplines. However, it is possible to perceive that it has a lack of systematization and organization of this content in the school, thus making it difficult the education of this cultural manifestation. The objective of the following study is to consider a curricular organization for the education of the fights and martial arts, which had been classified in accordance with its origin: Orientals and Occidental, being able to be "of grasp" and "she exempts" with and without use of utensils. In this study it was looked to classificate the main fights and martial arts as well as in accordance with classifying them its origins and variations. It has each time more martial studies on the education of the fights and arts in the school, however many times, focusing the content with an end in itself exactly, that is, aiming at only the execution of the movements. In this way, a curricular organization for this content comes to contribute for one better understanding of the fights and martial arts as a field of analysis and reflection, with subjects important to be studied, beyond facilitating to the planning and development of the lessons of Physical Education for this content.
Keywords: Physical Education; Education; Curricular Organization; Martial Arts